2010
DOI: 10.1089/apc.2010.0153
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nonadherence to Highly Active Antiretroviral Therapy Among HIV-Infected South Indians in Clinical Care: Implications for Developing Adherence Interventions in Resource-Limited Settings

Abstract: In light of the increasing availability of generic highly active antiretroviral therapy (HAART) in India, further data are needed to examine variables associated with HAART nonadherence among HIV-infected Indians in clinical care. We conducted a cross-sectional analysis of 198 HIV-infected South Indian men and women between January and April 2008 receiving first-line non-nucleoside reverse transcriptase inhibitor (NNRTI)-based HAART. Nonadherence was defined as taking less than 95% of HAART doses in the last 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 43 publications
8
45
2
Order By: Relevance
“…This was consistent with the study by Venkatesh et al who showed that demographic characteristics, such as age, gender, occupation, and residential status, did not predict treatment adherence. 17 In this study, education of caretaker (p=0.005) and employment (p=0.016) was positively associated with adherence. Higher education level was associated with better understanding regarding ART regimens and effective counselling was possible in them.…”
Section: Discussionmentioning
confidence: 47%
“…This was consistent with the study by Venkatesh et al who showed that demographic characteristics, such as age, gender, occupation, and residential status, did not predict treatment adherence. 17 In this study, education of caretaker (p=0.005) and employment (p=0.016) was positively associated with adherence. Higher education level was associated with better understanding regarding ART regimens and effective counselling was possible in them.…”
Section: Discussionmentioning
confidence: 47%
“…However, study done in Cameroon found that drinking alcohol was associated with non-adherence [9]. A study done in South India also indicated the association of alcohol use with non-adherence [47]. A study done in London showed that alcohol use were associated with an increased risk of non-adherence [41].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, study done in South Africa showed that alcohol use is independently associated with antiretroviral adherence [46]. Study done in South India also indicated the association of alcohol use with non-adherence [47]. Similarly, alcohol dependence was a significant predictor of non-adherence only in women [42].…”
Section: Alcohol Drinkers and Non-adherence To Antiretroviral Therapymentioning
confidence: 92%
“…Some of these early studies were later summarized in a systematic review on the impact of ART on sexual risk behavior [59]. A study conducted among HIV-infected Indians in care documented an association between ART and sexual abstinence, as well as an association between desire for having children and unprotected sex [46,60]. A national survey in the Cameroon found that not being on ARTwas associated with an over two-fold higher rate of inconsistent condom use [47], which also held for those who reported a partner who was HIV-uninfected or of unknown status [48].…”
Section: Assessing the Relationship Between Antiretroviral Therapy Usmentioning
confidence: 99%